Political discourse and Islam: Role of rhetoric in Turkey - Shukri, Syaza Farhana Mohamad; Hossain, Ishtiaq (George Mason University, Washington DC, USA, 2017)
The Adalet ve Kalkinma Partisi (AKP, Justice and Development Party) in Turkey has been blamed for Islamizing Turkish society. Its conservative policies spring from ideas similar to those expressed in Islamic writings. However, the AKP government has maintained that it abides by Turkish laicism. This paper analyses the extent the leaders’ rhetoric has changed over the years. This is done to find out whether the party truly intends to Islamize Turkey as part of a strategy to win votes. The paper highlights how the changes are related to the current national mood and issues, and concludes that the AKP cannot be said to have always intended to turn Turkey into a religious country. During the past 13 years the leaders’ rhetoric has shifted to reflect the support the Party receives either from conservative Turks or allies abroad. The leaders have yet to be consistent in its rhetoric to subvert the secular establishment for the implementation of Islamic laws.